2013
DOI: 10.1111/jog.12167
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes and quality of life post‐synthetic mesh‐augmented repair for pelvic organ prolapse in the Chinese population

Abstract: The synthetic polypropylene mesh is effective in treating POP and may improve QOL with no significant difference in the sexual life postoperatively. De novo stress urinary incontinence may occur after synthetic mesh-augmented repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[17] This result was possibly relevant to the unidentified defect during operation. Nevertheless, previous studies reported that the recurrence rate of synthetic mesh repair was 4%–15%,[1819] which was much lower than that after SIS repair. The reason for the variance might be the better stability of synthetic mesh.…”
Section: Discussionmentioning
confidence: 91%
“…[17] This result was possibly relevant to the unidentified defect during operation. Nevertheless, previous studies reported that the recurrence rate of synthetic mesh repair was 4%–15%,[1819] which was much lower than that after SIS repair. The reason for the variance might be the better stability of synthetic mesh.…”
Section: Discussionmentioning
confidence: 91%
“…Synthetic meshes include non-absorbable, absorbable and composite meshes, and common complications include recurrence and infection. The recurrence rate ranges from 10 to 24% 5 while the infection rate is in the 0.5–9.0% range 6 , which has led to a bottleneck in the development of hernia surgery methods 7 10 . Biomaterial meshes include xenogeneic acellular dermal matrix and allogenic acellular dermal matrix meshes.…”
Section: Introductionmentioning
confidence: 99%